2014
DOI: 10.1080/17508487.2014.922489
|View full text |Cite
|
Sign up to set email alerts
|

‘When saying you care is not really caring’: emotions of disgust, whiteness ideology, and teacher education

Abstract: Drawing on one of the author's experiences of teaching white teacher candidates in an urban university, this paper argues for the importance of interrogating the ways that benign emotions (e.g., pity and caring) are sometimes hidden expressions of disgust for the Other. Using critical race theory, whiteness studies, and critical emotion studies, it is shown how whiteness ideology erroneously translates disgust for people of color to false professions of pity or caring. This phenomenon is particularly interesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(88 citation statements)
references
References 36 publications
(39 reference statements)
0
88
0
Order By: Relevance
“…In other words, a merely technical pedagogical perspective on student teachers' development, without acknowledging the essential role of the self-understanding runs the risk of simply missing the point or -even worse-of unconsciously contributing to existing practices and structures of inequality, injustice and oppression . An example of the subtle perversity in which emotions and the politics may be intertwined can be found in a study by Matias and Zembylas ( 2014 ) in the USA. They found that in teacher education a particular emotion may be disguised into another and as such may jeopardize efforts to train future teachers with the ideals of social justice and equity.…”
Section: Emotions and Self-understandingmentioning
confidence: 97%
“…In other words, a merely technical pedagogical perspective on student teachers' development, without acknowledging the essential role of the self-understanding runs the risk of simply missing the point or -even worse-of unconsciously contributing to existing practices and structures of inequality, injustice and oppression . An example of the subtle perversity in which emotions and the politics may be intertwined can be found in a study by Matias and Zembylas ( 2014 ) in the USA. They found that in teacher education a particular emotion may be disguised into another and as such may jeopardize efforts to train future teachers with the ideals of social justice and equity.…”
Section: Emotions and Self-understandingmentioning
confidence: 97%
“…Matias and Zembylas () further explore White racial emotions of preservice teachers. This time, the analysis focuses on one class where the instructor specifically inserts explorations of Whiteness and emotions into the course syllabus.…”
Section: Interpersonal Whiteness and Higher Educationmentioning
confidence: 99%
“…Like Matias and Zembylas (2014), the goal was to delve more deeply into why white teacher candidates continue to express pity (the socially-acceptable emotional display) to people of color while still exhibiting guilt, anger, and defensiveness when learning antiracist pedagogies (the commonly-expressed emotions in whiteness). If one is not emotionally-prepared to undertake antiracist teaching practices, then it stands to reason s/he will not be emotionally secure enough to engage in long-term racial justice in her/his teaching.…”
Section: Emotionality (Emotional Investment): Feeling and Owning Our mentioning
confidence: 99%